Evidence for a functional subdivision of Premotor Ear-Eye Field (Area 8B) - Lanzilotto, Marco; Perciavalle, Vincenzo; Lucchetti, Cristina (Frontiers in Behavioral Neuroscience, 2015)
The Supplementary Eye Field (SEF) and the Frontal Eye Field (FEF) have been described as participating in gaze shift control. Recent evidence suggests, however, that other areas of the dorsomedial prefrontal cortex also influence gaze shift. Herein, we have investigated electrically evoked ear- and eye movements from the Premotor Ear-Eye Field, or PEEF (area 8B) of macaque monkeys. We stimulated PEEF during spontaneous condition (outside the task performance) and during the execution of a visual fixation task (VFT). In the first case, we functionally identified two regions within the PEEF: a core and a belt. In the core region, stimulation elicited forward ear movements; regarding the evoked eye movements, in some penetrations, stimulation elicited contraversive fixed-vectors with a mean amplitude of 5.14°; while in other penetrations, we observed prevalently contralateral goal-directed eye movements having end-points that fell within 15° in respect to the primary eye position. On the contrary, in the belt region, stimulation elicited backward ear movements; regarding the eye movements, in some penetrations stimulation elicited prevalently contralateral goal-directed eye movements having end-points that fell within 15° in respect to the primary eye position, while in the lateral edge of the investigated region, stimulation elicited contralateral goal-directed eye movements having end-points that fell beyond 15° in respect to the primary eye position. Stimulation during VFT either did not elicit eye movements or evoked saccades of only a few degrees. Finally, even though no head rotation movements were observed during the stimulation period, we viewed a relationship between the duration of stimulation and the neck forces exerted by the monkey’s head. We propose an updated vision of the PEEF composed of two functional regions, core and belt, which may be involved in integrating auditory and visual information important to the programming of gaze orienting movements.